Caribbean women in agriculture (FAO SantiagoCL, 1988)
Examines the historical factors which helped shape the situation of women in agriculture and rural employment in the Region through a case study on women's participation in sugar plantations in Trinidad and Tobago. Analyses the socio-economic situation of women under agricultural production systems. Focuses on the institutional framework in the Caribbean countries to provide action for 'women in development'. Presents an overview of legislation in four Caribbean countries viz Barbados, Belize, Guyana and St. Lucia and provides five case studies in Caribbean countries.
DC